2021
DOI: 10.1089/mdr.2019.0395
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Determinants of Antimicrobial Resistance in Clinical Isolates of Staphylococcus haemolyticus from India

Abstract: Aims: Although Staphylococcus haemolyticus is considered as a part of normal skin flora, infections associated with them are increasing. Irrespective of the low virulence profile it poses a severe threat to patients with indwelling devices due to its multidrug-resistant nature. The aim of this study was to determine antibiotic resistance patterns and to detect the genes responsible in clinical isolates of S. haemolyticus. Results: All the 356 S. haemolyticus isolates were susceptible to glycopeptides. 91.3% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…They found that 95% of the isolates were resistant to penicillin and ampicillin and 88% of the isolates were resistant to oxacillin and cefoxitin [80]. Similarly, Manoharan et al recorded that the susceptibility of 356 clinical isolates of S. haemolyticus to cefoxitin and penicillin was very low, 8.7% and 5.9%, respectively [81]. Likewise, De Vecchi et al showed that S. haemolyticus, isolated from joint infections, have the highest level of oxacillin resistance (83%), compared to S. aures and other CoNS species isolated from the same patients [82].…”
Section: β-Lactammentioning
confidence: 98%
“…They found that 95% of the isolates were resistant to penicillin and ampicillin and 88% of the isolates were resistant to oxacillin and cefoxitin [80]. Similarly, Manoharan et al recorded that the susceptibility of 356 clinical isolates of S. haemolyticus to cefoxitin and penicillin was very low, 8.7% and 5.9%, respectively [81]. Likewise, De Vecchi et al showed that S. haemolyticus, isolated from joint infections, have the highest level of oxacillin resistance (83%), compared to S. aures and other CoNS species isolated from the same patients [82].…”
Section: β-Lactammentioning
confidence: 98%
“…Interpretation was carried out according to the CLSI guidelines [ 18 ]. Isolates resistant to at least one agent in each of three or more classes of antimicrobials were classified as MDR [ 19 ].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…The first or latest cases of antibiotic resistance of chosen foodborne pathogens in different parts of the world. References [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%